Rhetorical pattern of the Indonesian EFL undergraduate students’ writings - Dian Fajrina; John Everatt; Amir Sadeghi (Universitas Syiah Kuala, 2022)
The present research aimed to study the rhetorical patterns in students’ writings, whether they follow a deductive pattern or an inductive pattern, and whether the pattern is similar when writing in English and the Indonesian language. The sample for this study was 20 undergraduate students from the Faculty of Teacher Training and Education majoring in English Education in several universities in Indonesia. Participants were requested to write two essays and two email-format letters, one of each was written in English, the other in the Indonesian language. The results showed that all students preferred the deductive pattern for their two types of essays. However, for the letter writing, students preferred the inductive pattern more than the deductive one, with 12 students using the inductive pattern in their letters in English and 16 students using the inductive pattern in their letters in Indonesian. It is suggested that the Indonesian culture and the teaching instructions received in the classrooms may influence students’ choice of the patterns they use in different types of writings. The findings should give valuable information for the design of teaching writing courses in English Education majors in Indonesia.